Application of Proteomics Approaches in the Identification of New Markers and Therapeutic Targets for Breast Cancer - Moh’d Hamadneh, Lama Abdel Qader (2008)
Breast cancer is the most common cancer in most parts of the world and is a leading cause of death among women. Even though the incidence of the disease is increasing each year, early detection and improved treatments have increased the survival rates. Currently, only a few markers are used for either early diagnosis, treatment response or for survival of breast cancer. In this study, two-dimensional gel electrophoresis (2DGE) was used in the quest for new potential biomarkers for the disease. Breast cancer cell lines and normal breast cell line were used to optimize the conditions to produce the respective proteome maps. Fresh frozen samples representing tumor and adjacent normal tissues were then collected from patients who underwent breast surgery at HUKM, HKL and Hospital Putrajaya. A total of sixty samples representing tumor and adjacent normal tissues were collected from June 2005 to December 2006 and were screened using 2DGE. Subsequently, 24 samples representing the different stages of infiltrating ductal carcinoma were used for further analysis using 17 cm IPG strips with 2 pH ranges 3-10 and 4-7, and the gels were analyzed using PDQuest 7.3 software. Several protein spots of interest were then excised and analyzed using MALDI-TOF spectrometer. Tumor rejection antigen (gp96), heat shock protein 90α, nucleosome assembly protein 1-like 1 and opioid-binding cell adhesion molecule precursor were identified and found to be upregulated in breast cancer cell lines when compared to the normal breast cell line. Calreticulin, tumor rejection antigen (gp96), heat shock protein 60 and cytokine induced apoptosis inhibitor 1 were found to be up-regulated by 2 folds or more in tumor tissues when compared to the adjacent normal tissues. On the other hand, actin γ 2 and protein tyrosine phosphatase were found to be down-regulated in tumor tissues. Since Calreticulin, a calcium binding protein was more intense at different stages of the disease with its expression confirmed by Western blotting, it was chosen for further investigations. Quantitative RT-PCR with GAPDH as a house keeping gene was used to monitor the level of gene expression and to correlate the mRNA levels with calreticulin levels. In the samples that represent later stages of the disease, mRNA levels were found to be highly expressed in tumor tissues when compared to the adjacent normal tissues where in average more than 18 folds increase was observed. The mRNA level was also found to be decreased in stage IV sample where 12 folds increase was observed, indicating a possible role of calreticulin in the progression of the disease. In conclusion, the proteomics approaches were utilized in this study and was found to be valuable in the search for potential new biomarkers for breast cancer.